The role of intraurethral alprostadil as a first-choice erectile dysfunction treatment option in special populations: a proposed treatment algorithm. (March 2014) - Dinsmore, Wallace; Lopes, Tomé Manuel; Potempa, Axel-Jürg; Piha, Juhana; Costa, Pierre
Various pharmacological treatment options exist for patients with erectile dysfunction (ED), including agents for oral, intraurethral or intracavernosal administration. Oral phosphodiesterase type 5 (PDE5) inhibitors, the current first-line therapy, have failure rates of up to approximately 60% or are contraindicated in some patients. Intracavernosal injections, considered the most effective nonsurgical ED treatment, also represent the most invasive option; they are associated with significantly more side effects than other ED therapies and have the highest potential for priapism, requiring physicians to have a management plan to counter this complication, and leading to low patient compliance. The use of invasive injections prior to less invasive options is also contrary to current US recommendations, which advocate the progressive use of less invasive methods before using invasive procedures. Based on these features, invasive intracavernosal injection should be considered as a later treatment option after other alternatives have been ruled out. A significant body of evidence demonstrates the efficacy and safety of minimally invasive intraurethral alprostadil, as monotherapy or combined with other pharmacological agents, in ED management. In particular, intraurethral alprostadil demonstrates efficacy in specific patient populations with ED (that are not suitable for PDE5 inhibitors), including those with diabetes, vascular disease, neuropathy, and alcohol/tobacco abuse, after radical prostatectomy or spinal cord injury, and in soft glans syndrome. We consider that intraurethral alprostadil provides a minimally invasive, safe and effective first treatment option after oral PDE5 inhibitors and a first-choice option in specific populations who cannot, for any reason, take PDE5 inhibitors, thus covering the unmet medical gap for less invasive therapy.